2020
DOI: 10.1080/16878507.2020.1828020
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of X-ray room shielding in diagnostic radiology using PHITS code

Abstract: This research was conducted to evaluate scatter distribution at an X-ray room for diagnostic radiography using the Particle and Heavy Ion Transport code System (PHITS). The X-ray room was simulated using PHITS code based on the imaging room distance and length, as well as the control console room. The exact dimensions of the rooms were used as a geometry code in PHITS to simulate a point source isotopically with 100 keV energy in the X-ray room. There are three sources situated for this study which are source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Furthermore, previous studies have shown that MC can be used in the evaluation of X-rays transmission through some shielding materials,[ 11 ] evaluation of the attenuation coefficient of personal radiation shielding protective clothing,[ 20 ] determination of shielding properties of concrete,[ 21 ] shielding analysis,[ 22 ] and the simulation of X-ray room shielding in diagnostic radiology. [ 23 ] However, there is a paucity of information on the application of the EGSnrc MC code in the design of radiotherapy bunker and evaluation of radiation protection around the facility.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have shown that MC can be used in the evaluation of X-rays transmission through some shielding materials,[ 11 ] evaluation of the attenuation coefficient of personal radiation shielding protective clothing,[ 20 ] determination of shielding properties of concrete,[ 21 ] shielding analysis,[ 22 ] and the simulation of X-ray room shielding in diagnostic radiology. [ 23 ] However, there is a paucity of information on the application of the EGSnrc MC code in the design of radiotherapy bunker and evaluation of radiation protection around the facility.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies conducted since 1970 have proved that lead (Pb-82) is effective in photon attenuation either to shield the emission of photons from radioactive sources or as a shielding material for the wall of an irradiation facility room[ 1 2 3 ] such as for diagnostic and radiotherapy room. However, the disadvantages of lead, along with its advantages, are the lead material itself is toxic and expensive.…”
Section: Introductionmentioning
confidence: 99%